Indigeneity and Disabilities in the Ecuadorian Oral History Archives - Scott Thomas Gibson; Sara Newman; Antonia Carcelen-Estrada (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: oral history; Ecuador; Indigeneity; archive; Quijos